2012
DOI: 10.1093/brain/awr329
|View full text |Cite
|
Sign up to set email alerts
|

Visual activation of auditory cortex reflects maladaptive plasticity in cochlear implant users

Abstract: Cross-modal reorganization in the auditory cortex has been reported in deaf individuals. However, it is not well understood whether this compensatory reorganization induced by auditory deprivation recedes once the sensation of hearing is partially restored through a cochlear implant. The current study used electroencephalography source localization to examine cross-modal reorganization in the auditory cortex of post-lingually deafened cochlear implant users. We analysed visual-evoked potentials to parametrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
191
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(224 citation statements)
references
References 88 publications
27
191
1
5
Order By: Relevance
“…It has been assumed that visual language may compromise the ability of auditory brain regions to respond to sound after implantation (3,16) and that maladaptive cross-modal plasticity must be reversed for CI success (4). To explore the mechanisms underlying hearing restoration, we examined whether an increase in responsiveness of auditory brain regions to auditory speech stimulation after implantation was dependent on a decrease in cross-modal activation to visual speech.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been assumed that visual language may compromise the ability of auditory brain regions to respond to sound after implantation (3,16) and that maladaptive cross-modal plasticity must be reversed for CI success (4). To explore the mechanisms underlying hearing restoration, we examined whether an increase in responsiveness of auditory brain regions to auditory speech stimulation after implantation was dependent on a decrease in cross-modal activation to visual speech.…”
Section: Resultsmentioning
confidence: 99%
“…This cross-modal plasticity within auditory cortex can provide adaptive benefits such as superior visual localization and motion detection abilities (2). On the other hand, cross-modal plasticity can limit a deaf individual's ability to understand speech after their hearing is restored with a cochlear implant (3,4). Therefore, it is assumed that this maladaptive cross-modal activation of auditory brain regions must decrease following cochlear implantation for speech understanding to be restored successfully (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in noisy surroundings, the speech understanding typically decreases remarkably in CI users (Hochmair-Desoyer et al, 1997;Wilson and Dorman, 2008;Zeng et al, 2011). In general, there is a high variability in speech recognition ability across CI users which is likely caused by factors related to the implant, the auditory nerve, and the reorganization of the central auditory system (Drennan and Rubinstein, 2008;Nadol et al, 1989;Sandmann et al, 2012Sandmann et al, , 3 2015. In particular, electrical hearing may require additional explicit processing due to a mismatch between the attributes of the current CI input and the attributes stored in the longterm memory (Finke et al, 2015;Rönnberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that greater dependency on the visual function performed by the occipito-temporal region due to auditory deprivation may interfere with the acquisition of auditory language [5] . Similarly, Sandmann et al [28] reported a visual takeover type of reorganization in the auditory cortex of cochlear implant users and that the extent of this cross-modal reorganization was systematically related to speech recognition ability with a cochlear implant. In other words, visual processing dominance was inversely related to speech recognition ability with a cochlear implant.…”
Section: Discussionmentioning
confidence: 88%